Extensive subclinical sinusitis leading to Moraxella osloensis meningitis. (2016) - Fox-Lewis, A.; Coltart, G.; Rice, S.; Sen, R.; Gourtsoyannis, Y.; Hyare, H.; Gupta, R.K.
Abstract: We report a case of a 31 year old male with extensive subclinical sinusitis leading to erosion in the cribriform plate and subsequent meningitis caused by the organism Moraxella osloensis . The patient presented to the emergency department with rapid onset confusion, neck stiffness and headache. Inflammatory markers, renal and liver function, and a chest radiograph were all normal. CT Head showed extensive polyp disease in the paranasal sinuses with expansion of the left frontal sinus and CT Sinuses revealed an area of low attenuation in the cribriform plate consistent with bony erosion. MRI Head showed thick loculated sinus inflammation. Lumbar puncture yielded CSF with a high white cell count of predominantly mononuclear cells, no visible organisms and an elevated protein. CSF microscopy, culture and viral PCR were not diagnostic, and so the CSF was sent for 16S rDNA PCR screening, which identified the rDNA of Moraxella osloensis . Moraxella osloensis is a rare cause of bacterial meningitis, with only a few reported cases. This case illustrates that sinusitis, while a common condition, when severe can predispose to intracranial infection with atypical and low virulence organisms such as Moraxella species, which do not commonly cause invasive CNS disease. This case represents the first case of Moraxella osloensis meningitis reported from the United Kingdom.